2013
DOI: 10.2478/v10222-012-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cereal Beta-D-Glucan Hydrocolloids and their Effect on Bread and Ketchup Parameters

Abstract: Microbiological and sensory evaluations of bread and ketchup supplemented with β-D-glucan hydrogels isolated from wheat, oat, barley, and rye were carried out. Adding hydrocolloids did not affect sensory parameters of bread negatively; moreover rye and oat β-D-glucans improved the total tastiness of bread. Water activity values in fortifi ed breads showed β-D-glucans, except isolated from oat, as elements moderately increasing this parameter and subsequently increasing also bread freshness during the storage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…According to the results, absorbance spectra for the control cookies (wheat flour) and 1% -glucan fortified cookies were lower than the absorbance for the cookies made with 2 or 4% -glucan, suggesting that the -glucan incorporation in the cookies at 2 or 4% reduces freshness losses versus control cookies or cookies made with 1% -glucan ( Figure 3). Present findings are supported by Havrlentová et al [48] who analyzed bread and ketchup (having -D-glucan hydrogels) prepared with wheat, oat, barley, and rye. They reported bread freshness during the storage which was possible due to the addition of -D-glucan barley and rye.…”
Section: Near-infrared Spectroscopy: Spectra Measurementssupporting
confidence: 87%
“…According to the results, absorbance spectra for the control cookies (wheat flour) and 1% -glucan fortified cookies were lower than the absorbance for the cookies made with 2 or 4% -glucan, suggesting that the -glucan incorporation in the cookies at 2 or 4% reduces freshness losses versus control cookies or cookies made with 1% -glucan ( Figure 3). Present findings are supported by Havrlentová et al [48] who analyzed bread and ketchup (having -D-glucan hydrogels) prepared with wheat, oat, barley, and rye. They reported bread freshness during the storage which was possible due to the addition of -D-glucan barley and rye.…”
Section: Near-infrared Spectroscopy: Spectra Measurementssupporting
confidence: 87%
“…[34][35][36] Havrlentova and Kraic noted a large variation in the content of β-glucan in barley and oat varieties in all genotypes and indicated that barley and oat may be convenient sources of β-glucan. 34 Based of the biochemical analysis of the β-glucan content in the investigated oat and barley varieties, it could be concluded that the content of β-glucan was higher in the barley varieties than in the oat varieties, which could be observed through the average value of the β-glucan contents (6.6 % of the dry weight of the grain in the analyzed barley varieties, but only 4.65 % of the dry weight of the grain of the analyzed oat varieties). In the tested barley varieties, the β-glucan content ranged from 3.52 to 7.81 % of the dry grain weight, while the β-glucan content of analyzed oat varieties ranged from 3.15 to 7.28 % of the dry grain weight.…”
Section: The Content Of β-Glucans In Barleymentioning
confidence: 99%
“…Out of cereals, the highest amounts of β-glucans are found in barley and oat grains (Havrlentová & Kraic 2006). The FDA determined that an effective daily intake of β-glucan is 3 g, but there have been few attempts to establish a dose response (which may differ among different subject groups and depend upon baseline level).…”
Section: Dietary Fi Brementioning
confidence: 99%